2019
DOI: 10.3389/fimmu.2019.02616
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Gene Expression Dataset Re-analysis Reveals Variability in Influenza Infection and Vaccination

Abstract: Influenza, a communicable disease, affects thousands of people worldwide. Young children, elderly, immunocompromised individuals and pregnant women are at higher risk for being infected by the influenza virus. Our study aims to highlight differentially expressed genes in influenza disease compared to influenza vaccination, including variability due to age and sex. To accomplish our goals, we conducted a meta-analysis using publicly available microarray expression data. Our inclusion criteria included subjects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 86 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…Several studies demonstrate that gene expression is altered after natural influenza infection or vaccination. The inter-individual variability observed after natural infection or vaccination can be explained by inter-individual differences in gene expression in airway epithelial cells and immune cells ( 121 ). Alcorn et al showed that these gene expression changes are transient in time with different differentially expressed genes at three and seven days after vaccination compared to pre-vaccination expression profiles ( 122 ).…”
Section: Methods To Assess Cell-mediated Immunitymentioning
confidence: 99%
“…Several studies demonstrate that gene expression is altered after natural influenza infection or vaccination. The inter-individual variability observed after natural infection or vaccination can be explained by inter-individual differences in gene expression in airway epithelial cells and immune cells ( 121 ). Alcorn et al showed that these gene expression changes are transient in time with different differentially expressed genes at three and seven days after vaccination compared to pre-vaccination expression profiles ( 122 ).…”
Section: Methods To Assess Cell-mediated Immunitymentioning
confidence: 99%
“…Systemic biology approaches were applied to study the complexity problem of molecular signatures after vaccination, which was largely confounded by the presence of various leukocyte subpopulations in clinical samples, as reviewed by Pezeshki et al [ 9 ]. Previous studies of TA after vaccination were limited to either focusing on the genetic determinants of responders or the difference between vaccination and a full-blown infection [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…So, the results are convoluted and confounded by different proportional cell counts of each of the cell subpopulations in these cell mixture samples. The research community has called for new biomarkers to enhance vaccine development, particularly in view of the current COVID-19 pandemic [ 9 , 10 , 11 , 12 ]. Here, we are interested to know if B lymphocyte TA could be a reliable early predictor for subsequent seroconversion of B lymphocyte as the precursor of plasma cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous analyses of transcriptional responses after RTS,S vaccination revealed strong AS01-driven peripheral innate immune activation and candidate protection-associated signatures for individual studies (17)(18)(19)(20)(21). While biomarker development and understanding of pathogenesis for other infectious diseases have been accelerated by multi-cohort transcriptional analyses (22)(23)(24)(25), a multi-study transcriptional analysis of RTS,S-mediated protection in CHMI has not been undertaken. Identification of simple, yet robustly predictive, signatures of RTS.S clinical activity would facilitate evaluation of additional alternative malaria vaccine regimens, providing preclinically testable hypotheses about the RTS,S mode of action and refining candidate correlative variables for testing in field studies.…”
Section: Introductionmentioning
confidence: 99%